In vitro propagation of Vriesea incurvata: conservation of a bromeliad endemic to the Atlantic Forest - Sasamori, Márcio Hisayuki; Júnior, Delio Endres; Droste, Annette (Iheringia, Série Botânica., 2018)
Vriesea incurvata is an epiphytic bromeliad of the Atlantic Forest with ornamental attributes that encourage extractivism. This study assessed the influence of sucrose (10, 30 and 60 g L-1) on the survival and development of V. incurvata plantlets cultivated for 180 days on MS medium and acclimatizated for 150 days under controlled conditions. Survival of 100% was recorded in all in vitro treatments. Sucrose at concentration of 60 g L-1 provided highest length of the aerial portion and of the longest root, greatest number of leaves and roots, highest fresh mass and lowest contents of chlorophylls and carotenoids. The higher sucrose concentration also positively influenced the development of plantlets ex vitro, allowing for increased averages for the parameters assessed. The results indicate micropropagation as an alternative by which V. incurvata plantlets may be provided for commercial means, reducing the extractivism from natural populations, or for reintroduction into their natural habitat.